Studenteroprøret i Danmark - Jensen, Steven L. B.; Jørgensen, Thomas Ekman (Historisk Tidsskrift, 2013)
The Student Revolt in DenmarkIn the 1960s central governmental authorities in Denmark initiated certain attempts to modernise the universities and introduce democratic reforms into a system where decisions, large and small alike, were exclusively in the hands of the professors, a title and position possessed by relatively few faculty members. The initiatives foundered, however, on the unwillingness of the professors to relinquish their authority. The reaction of the psychology students to this professorial obstructionism is clearly marked in the proposals they put forward to gain influence over their studies. After inadequate reform attempts had dragged on for some years, in the Spring of 1968 frustration erupted into revolt against both professorial rule and submissive student politics. The psychology students took a confrontational stance, abandoning the "realistic" line of negotiation in favour of direct action and demands for radical changes. They found support in the Rector of the University of Copenhagen, Mogens Fog, himself an earnest reformer, and broadly backed by students throughout the whole university. This resulted with astonishing speed in a powerful activist movement that pressed the sluggish reform efforts to a head. After the summer holidays in 1968 the unorganised activist movement was given a more formal frame-work through the Student Council, where the leading posts were packed with activists. At the same time, students at a number of institutes began to organise their own forms of action and alternative teach-ins. Out of this grew a genuine student movement with its own political and university agenda, which gradually became more radical.Radicalisation and the unexpected success led, however, to overconfidence when it came to translating the reforms into a new statute on governing the universities. The student movement followed an activist all-or-nothing line, which alienated its allies and ended in a political fiasco for the movement. In spite of that, the end-result has none the less been recognised by posterity as the world's most liberal university-government law.Translated by Michael Wolfe